Bilateral Carotid-Cavernous Fistulas: An Uncommon Cause of Pituitary Enlargement and Hypopituitarism - Anthony Liberatore; Ronald M. Lechan (Case Reports in Endocrinology)
Carotid-cavernous fistulas (CCFs) are rare, pathologic communications of the carotid artery and the venous plexus of the cavernous sinus. They can develop spontaneously in certain at risk individuals or following traumatic head injury. Typical clinical manifestations include headache, proptosis, orbital pain, and diplopia. We report a case of bilateral carotid-cavernous fistulas associated with these symptoms and also with pituitary enlargement and hypopituitarism, which improved following surgical intervention. Arterialization of the cavernous sinus and elevated portal pressure may interfere with normal venous drainage and the conveyance of inhibiting and releasing hormones from the hypothalamus, resulting in pituitary enlargement and hypopituitarism. This condition should be considered in the differential diagnosis of hypopituitarism associated with anterior pituitary enlargement.